Pelatihan Dan Pendampingan Penyusunan Laporan Keuangan Menuju Desa Mandiri (Gabungan Kelompok Tani Torong Makmur Kota Batu) - Novitasari Agus Saputri; Ike Arisanti (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
The purpose of this service is to provide training and assistance to partners related to the preparation of financial reports at Gapoktan Torong Makmur so that in the future determining the appropriate tax rate. The method we use is training and mentoring. The output that will be produced is in the form of a financial report. So that prior to the existence of financial statement assistance, it had not been prepared in accordance with accounting standards, then after the assistance in financial statements was in accordance with generally accepted accounting standards.